Selected effects of combined oral contraceptives use - Bogucka, Julia; Brzyska, Anna; Domańska, Natalia; Bojarska, Małgorzata; Wilczek, Natalia; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction and objective:: Combined oral contraceptives (COCs) are one of the most popular methods of contraception worldwide. The universality of this method leads to the constant analysis of its influence on the female body. The purpose of this study is to discuss selected side effects of COC use. Review methods: In July 2022, articles found in the Medline (Pubmed) and Google Scholar databases were selected by using the following keywords: oral contraceptive use; risk of cancer; depression; side effects of hormonal contraception; venous thrombosis. Brief description of the state of knowledge: COC use has been shown to be associated with a 2-6 fold increase in the risk of developing venous thromboembolism (VTE). The component responsible for this side effect was initially thought to be synthetic estrogen - ethinylestradiol. It is now recognized as having the greatest influence on mood disorders. An increased risk of cancer has been reported in women taking COCs in case of breast cancer and liver cancer. Inverse relationship was observed in colorectal cancer, ovarian cancer and endometrial cancer. Summary: COC use can have side effects, but it also has many health benefits. Therefore, it is important to constantly learn about this topic and minimize the risk of adverse side effects.